Update in Molecular Aspects and Diagnosis of Autoimmune Gastritis - Masaya Iwamuro; Takehiro Tanaka; Motoyuki Otsuka (Current Issues in Molecular Biology, 2023)
Recent studies have advanced our understanding of the pathophysiology of autoimmune gastritis, particularly its molecular aspects. The most noteworthy recent advancement lies in the identification of several candidate genes implicated in the pathogenesis of pernicious anemia through genome-wide association studies. These genes include PTPN22, PNPT1, HLA-DQB1, and IL2RA. Recent studies have also directed attention towards other genes such as ATP4A, ATP4B, AIRE, SLC26A7, SLC26A9, and BACH2 polymorphism. In-depth investigations have been conducted on lymphocytes and cytokines, including T helper 17 cells, interleukin (IL)-17A, IL-17E, IL-17F, IL-21, IL-19, tumor necrosis factor-α, IL-15, transforming growth factor-β1, IL-13, and diminished levels of IL-27. Animal studies have explored the involvement of roseolovirus and H. pylori in relation to the onset of the disease and the process of carcinogenesis, respectively. Recent studies have comprehensively examined the involvement of autoantibodies, serum pepsinogen, and esophagogastroduodenoscopy in the diagnosis of autoimmune gastritis. The current focus lies on individuals demonstrating atypical presentations of the disease, including those diagnosed in childhood, those yielding negative results for autoantibodies, and those lacking the typical endoscopic characteristics of mucosal atrophy. Here, we discuss the recent developments in this field, focusing on genetic predisposition, epigenetic modifications, lymphocytes, cytokines, oxidative stress, infectious agents, proteins, microRNAs, autoantibodies, serum pepsinogen, gastrin, esophagogastroduodenoscopy and microscopic findings, and the risk of gastric neoplasm.